STUDY ON FUNCTIONAL INGREDIENTS AND CLAIMS OF READY TO DRINK (RTD) FRUIT JUICE IN MODERN RETAIL - Fadlillah, Hendry Noer; Nurkhoeriyati, Tina; Felanesa, Lira; Utomo, Andika Wahyu (Journal Akademik Universitas Swiss German, 2019)
Fruit juices are well known as healthy food.  Consumers consume fruit juices not only to get refreshment, but also to get health benefits. The aims of this research are to identify health-related claims in juices and functional ingredients used to meet the regulation on claim requirement. The research was conducted by collecting RTD (ready to drink) juice in modern retail. All of the information on the label is recorded, identified, and classified based on regulation document, then processed and analyzed statistically. The result show, 70% of product samples provide claims on the label.  Claim on vitamin C is the most favorite one. As much as 52% of claimed products contain vitamin C ? related claim. After vitamin C, the next popular claims are regarding dietary fiber (11%) and vitamin A (10%).  Interestingly, 63% of claimed products provide more than one nutrient claims. They combine two or more nutrients content as the claim, such as vitamin C and vitamin A, fiber and vitamin C, etc. There is 20% of RTD fruit juice enriched or fortified by functional ingredients, mostly in vitamin premix.  It means, claims are not only given by addition of functional ingredients from the outside.  RTD juice industries are still able to provide the claim, without fortification or enrichment, if they can maintain the nutrient content of raw material to meet requirement of regulation on claim.